2015
DOI: 10.1088/0026-1394/52/2/195
|View full text |Cite
|
Sign up to set email alerts
|

Precision measurement of a potential-profile tunable single-electron pump

Abstract: We performed a precision measurement of the current from a single-parameter electron pump, where the potential-profile for a quantum dot was manipulated by multiple top-metal gates. In an optimally tuned condition, driven with a sinusoidal-waveform microwave at f = 0.95 GHz, B = 11 T, and T = 0.3 K, the relative deviation of the pump current from ef, δI p /ef ≡ (I p − ef)/ef was measured to be (−0.92 ± 1.37) ppm. Our experiment reproduces the current quantisation accuracy of a previous measurement of a single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
57
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 16 publications
(46 reference statements)
3
57
0
Order By: Relevance
“…2(b) and 2(e) we show P N ðV G2L Þ for 0 N 3, obtained from sets of 500 cycles for each V G2L using the slow and fast loading waveforms, respectively. As expected from DC measurements with the pump in a magnetic field, 5,7,8,20 there are a series of wide plateaus where one value of N dominates the loading statistics. This is highlighted by color-coding data points black when all the cycles yielded the same value of N. Comparable data have been presented previously, 9 but at zero magnetic field where the regime of very accurate loading could not be accessed.…”
supporting
confidence: 54%
See 3 more Smart Citations
“…2(b) and 2(e) we show P N ðV G2L Þ for 0 N 3, obtained from sets of 500 cycles for each V G2L using the slow and fast loading waveforms, respectively. As expected from DC measurements with the pump in a magnetic field, 5,7,8,20 there are a series of wide plateaus where one value of N dominates the loading statistics. This is highlighted by color-coding data points black when all the cycles yielded the same value of N. Comparable data have been presented previously, 9 but at zero magnetic field where the regime of very accurate loading could not be accessed.…”
supporting
confidence: 54%
“…In one example, a dynamically gated QD can pump electrons from a source to a drain electrode, [1][2][3][4] generating an accurate quantized current with metrological application as a new realisation of the ampere. [5][6][7][8] In this application, the accuracy of electron trapping and ejection in the non-adiabatic regime is of key importance. We wish to transfer n electrons in response to a single gate voltage cycle, with an error rate less than 10 À7 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[8][9][10][11][12] Also, spin pumping in graphene devices [13][14][15][16][17][18] and adiabatic pumping [19][20][21] were studied recently. It has been reported that the quantized current pumping can be achieved by applying periodic voltage modulation on a quantum dot gate.…”
Section: Introductionmentioning
confidence: 99%